2012
DOI: 10.1177/0049124112460373
|View full text |Cite
|
Sign up to set email alerts
|

ML Versus MI for Missing Data With Violation of Distribution Conditions

Abstract: Normal-distribution-based maximum likelihood (ML) and multiple imputation (MI) are the two major procedures for missing data analysis. This article compares the two procedures with respects to bias and efficiency of parameter estimates. It also compares formula-based standard errors (SEs) for each procedure against the corresponding empirical SEs. The results indicate that parameter estimates by MI tend to be less efficient than those by ML; and the estimates of variance-covariance parameters by MI are also mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 46 publications
6
74
1
1
Order By: Relevance
“…Our prior simulation study (Hallgren & Witkiewitz, 2013) also found that the MI and FIML methods produced less biased estimates of alcohol treatment outcomes regardless of sample size and that a larger sample size does not protect against bias when using single imputation methods (e.g., LOCF; missing = heavy drinking). Importantly, we found both in the current study and in our prior work (Hallgren & Witkiewitz, 2013) that MI and FIML produced similar standard errors and seemed to perform equally well in recovering the truth, which is inconsistent with prior studies that have found MI to produce biased estimates when distributional assumptions are violated, particularly for smaller sample sizes (Demirtas et al, 2008; Yuan et al, 2012). …”
Section: Discussioncontrasting
confidence: 99%
“…Our prior simulation study (Hallgren & Witkiewitz, 2013) also found that the MI and FIML methods produced less biased estimates of alcohol treatment outcomes regardless of sample size and that a larger sample size does not protect against bias when using single imputation methods (e.g., LOCF; missing = heavy drinking). Importantly, we found both in the current study and in our prior work (Hallgren & Witkiewitz, 2013) that MI and FIML produced similar standard errors and seemed to perform equally well in recovering the truth, which is inconsistent with prior studies that have found MI to produce biased estimates when distributional assumptions are violated, particularly for smaller sample sizes (Demirtas et al, 2008; Yuan et al, 2012). …”
Section: Discussioncontrasting
confidence: 99%
“…For the bias and RMSE of the intercept mean, the non-normal degree had no impact on the two methods. For the slope mean, the bias and RMSE of MAR-based ML method was not affected by the degree of non-normality, and the conclusions agree with previous studies (Enders, 2001; Tacksoo et al, 2009; Yuan et al, 2012). But the MNAR-based DK method was more greatly impacted by the non-normal degree.…”
Section: Discussionsupporting
confidence: 90%
“…Four levels of skewness and kurtosis were considered. In light of the degrees of non-normal distribution adopted by previous simulation studies (Yuan and Bentler, 2000; Enders, 2001; Tacksoo et al, 2009; Yuan et al, 2012), the skewness and kurtosis were set at 0 and 3 for normal data, 0.5 and 6 for the slightly non-normal case, 2 and 15 for the moderately non-normal case, and 3 and 33 for the extremely non-normal case, respectively.Two missingness mechanisms, i.e., MNAR and MAR, were involved.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple imputation is among the optimal options for handling missing data (Kline, 2005), yielding relatively unbiased estimates and performing particularly well relative to other approaches in small samples (Graham & Schafer, 1999; Yuan et al, 2012) and when flexibility in analytic strategies is required (Allison, 2003; Schafer, 1999). To capture changes in the mediator and outcome variables, residualized gain scores (Tucker, Damarin, & Messick, 1966) were calculated for pre- and post-treatment or -waitlist scores on the measures of emotion dysregulation, DSH, and BPD symptoms.…”
Section: Resultsmentioning
confidence: 99%